Upaya Meningkatkan Keefektifan Perfusi Jaringan Serebral pada Pasien CVA - Faradila, Eva; , Enita Dewi, S.Kep., Ns (2017)
Background: Stroke is one of the leading causes of death in the world and Indonesia ranked first in Asia. The prevalence in the world reached 15 million cases and increasing every year. While the incidence of stroke in Central Java in 2014 reached 0.57%. Stroke is a brain disorder caused by disturbances in the brain's neurons. Stroke become a big and serious problem. As the second largest cause of disability in people aged over 60 years, stroke cause psychosocial burden as well as a very large cost. Methods: The method used is descriptive case studies in stroke patients on February 18th-21st, 2017 covering five nursing process ranging from assessment, determine a diagnosis, intervention, implementation and evaluation. Data obtained from looking at medical records, observation, interview, physical examination and documentation of journals and books. Objectives: The general objective of this paper is to perform nursing care in patients with a diagnosis of cerebral tissue perfusion ineffective and report non-pharmacological therapy against loss of consciousness at Ny.S. To give an idea of the effort to improve the effectiveness of tissue perfusion in patients with CVA and to prevent tissue perfusion in stroke patients. Results: After the 3x24-hour nursing care for patients with cerebral tissue perfusion ineffective problem cerebral tissue perfusion, aspiration risk, impaired mobility, self-care deficit has not been resolved and the intervention should be continued. Four nursing problem is not resolved, this requiring further treatment and cooperation with other medical teams, patients, and families that are indispensable for the success of nursing care. Conclusion: The influence of non-pharmacological therapies against loss of consciousness before and after the intervention.